2016
DOI: 10.3390/v8010023
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of White Spot Syndrome Virus Infection and Perspectives on Treatments

Abstract: Since its emergence in the 1990s, White Spot Disease (WSD) has had major economic and societal impact in the crustacean aquaculture sector. Over the years shrimp farming alone has experienced billion dollar losses through WSD. The disease is caused by the White Spot Syndrome Virus (WSSV), a large dsDNA virus and the only member of the Nimaviridae family. Susceptibility to WSSV in a wide range of crustacean hosts makes it a major risk factor in the translocation of live animals and in commodity products. Curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
103
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(107 citation statements)
references
References 220 publications
1
103
0
3
Order By: Relevance
“…WSSV, a virus with a 305-kb circular double-stranded genomic DNA, is a new member of the genus Whispovirus belonging to the family Nimaviridae (20). WSSV is a major pathogen in shrimp and causes great economic losses in crustacean aquaculture industries worldwide (21). The results showed that WSSV genome-encoded miRNAs (WSSV-miR-N13 and WSSV-miR-N23) could simultaneously target the Dorsal gene of its host shrimp.…”
mentioning
confidence: 99%
“…WSSV, a virus with a 305-kb circular double-stranded genomic DNA, is a new member of the genus Whispovirus belonging to the family Nimaviridae (20). WSSV is a major pathogen in shrimp and causes great economic losses in crustacean aquaculture industries worldwide (21). The results showed that WSSV genome-encoded miRNAs (WSSV-miR-N13 and WSSV-miR-N23) could simultaneously target the Dorsal gene of its host shrimp.…”
mentioning
confidence: 99%
“…In shrimp farming, vaccine-like approaches to combat the white spot syndrome virus (WSSV) have been reported as being very successful [140,141]. Vaccination with inactivated viruses or recombinant virus proteins lead to an improved survival rate upon WSSV infection [142][143][144]. The application of transgenerational immune priming to reduce disease outbreaks has also been considered in the aquaculture industry [145].…”
Section: Immune Priming and Transgenerational Immune Primingmentioning
confidence: 99%
“…Mortality rates are usually very high and cumulative mortality can reach 100% within 3-10 days from the onset of visible gross signs [3,4]. The clinical symptoms of white spot syndrome include loss of appetite, lethargy, and the appearance of white spots on the exoskeleton [5]. White spot disease had been reported from several Asian countries since the early 1990s, and then from South America and from the south-eastern coast of the USA [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…During the breeding process, disease prevention and control measures are mostly based on prevention. Once the white spot disease breaks out, the crayfish's mortality rate is extremely high, which leads to the farmers' blood loss [5]. Therefore, there is an urgent need to develop a therapeutic drug that is less harmful to crayfish cells and could effectively reduce the mortality rate after infected WSSV.…”
Section: Introductionmentioning
confidence: 99%